Attitudes and Barriers to Breastfeeding among Mothers in Princess Nourah Bint Abdulrahman University, Riyadh, Kingdom of Saudi Arabia - Razan Yasser Abulreesh; Ibtihaj Abdullah Alqahtani; Zainah Yahya Alshehri; Maha Ali Alsubaie; Shatha Nasser Alburayh; Norah Mohammed Alzamil; Hayat Saleh Alzahrani (The Scientific World Journal)
Background. Breastfeeding provides unsurpassed natural nutrition to the newborn and infant. It has a nearly perfect mix of food elements and vitamins that infants need to grow up. Nonetheless, the tendency for breastfeeding remains below the expected levels. Objectives. To explore the attitudes and barriers to breastfeeding among mothers in Princess Nourah Abdulrahman University (PNU), Riyadh, Saudi Arabia. Methods. A cross-sectional study was conducted, from January to April 2019; 399 PNU students, employees, and faculty mothers aged 18 years and above with experience of childbirth and breastfeeding were included in the study using a predesigned validated questionnaire. The questionnaire consisted of four scales: sociodemographic, attitude toward breastfeeding, barriers to breastfeeding, and induced lactation knowledge. Results. The participants’ mean age was 34.1 ± 10.4 years; most (87.8%) were Saudi; 92.8% were married; 62% had a bachelor’s degree; and 43% had “enough income.” While 40% of the mothers reported >6 months “exclusive breastfeeding” for the first baby, only 34.8% did so for the last baby, and 54.5% did so for most of all babies altogether. The mothers’ parity ranged between 1 birth and 4 births in 23.5% and 17.5% of the participants, respectively. An overall score of breastfeeding attitude averaged 59.6 ± 7.3. The tendency for scoring a negative attitude to breastfeeding was significantly reported (p<0.5) among 127 (31.8%) 31- to 40-year-old mothers; 153 (38.3%) bachelor’s degree holders; and 157 (39.3%) employees (χ2 (4) 14.6, p = 0.006; χ2 (4) 10.4, p = 0.034; and χ2 (4) 20.4, p < 0.001, respectively). “Mother’s illness” was the most commonly (63%) reported barrier to “not to breastfeed,” followed by “work” (45.5%) and “father not supporting breastfeeding” (14.8%). Conclusions. An overall negative attitude toward breastfeeding among PNU mothers was noted. Barriers included mother’s sickness and work. Efforts to minimize such negative attitudes and barriers among susceptible mothers are warranted.